2020
DOI: 10.1038/s41467-020-14737-8
|View full text |Cite
|
Sign up to set email alerts
|

Klf5 acetylation regulates luminal differentiation of basal progenitors in prostate development and regeneration

Abstract: Prostate development depends on balanced cell proliferation and differentiation, and acetylated KLF5 is known to alter epithelial proliferation. It remains elusive whether posttranslational modifications of transcription factors can differentially determine adult stem/ progenitor cell fate. Here we report that, in human and mouse prostates, Klf5 is expressed in both basal and luminal cells, with basal cells preferentially expressing acetylated Klf5. Functionally, Klf5 is indispensable for maintaining basal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…In mouse prostates, castration-mediated androgen depletion increased Klf5-positive cells [29], which is seemingly inconsistent with the induction of KLF5 by androgen in PCa cells (Figure 1). Compared to luminal cells in the prostate, basal cells preferentially express Klf5, particularly acetylated Klf5 [30], castration causes massive death in luminal cells but much less so in basal cells, and basal cells express much less AR and are androgen insensitive. LNCaP and C4-2B cells are AR-positive and androgen-dependent/sensitive, and thus have a different lineage from basal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse prostates, castration-mediated androgen depletion increased Klf5-positive cells [29], which is seemingly inconsistent with the induction of KLF5 by androgen in PCa cells (Figure 1). Compared to luminal cells in the prostate, basal cells preferentially express Klf5, particularly acetylated Klf5 [30], castration causes massive death in luminal cells but much less so in basal cells, and basal cells express much less AR and are androgen insensitive. LNCaP and C4-2B cells are AR-positive and androgen-dependent/sensitive, and thus have a different lineage from basal cells.…”
Section: Discussionmentioning
confidence: 99%
“…A sphere formation assay was performed as previously described by Zhang et al (39) with slight modification. Falcon 8-well chamber slides (product no.…”
Section: Sphere Formation Assaymentioning
confidence: 99%
“…Our previous studies have demonstrated that TGF-β induces the acetylation of transcription factor Krüppel-like factor 5 (KLF5) at lysine 369 (K369) via SMAD-recruited p300 acetylase 38,39 , and acetylated KLF5 (Ac-KLF5) then forms a transcriptional complex different from that of deacetylated KLF5 (deAc-KLF5), which reverses the functions of deAc-KLF5 and is essential for TGF-β to function in gene regulation, cell proliferation, differentiation, and tumorigenesis [38][39][40][41][42] . Considering the established TGF-β/Ac-KLF5 signaling axis and the function of TGF-β in the induction of EMT, bone metastases, and chemoresistance, we hypothesize that Ac-KLF5 plays a crucial role in the development of chemoresistant bone metastases in PCa.…”
mentioning
confidence: 99%